Sources of variability in quantifying circulating thymosin beta-4: literature review and recommendations. (31st May 2018) - Tan, Warren K. Y.; Purnamawati, Kristy; Pakkiri, Leroy S.; Tan, Sock Hwee; Yang, Xiaoxun; Chan, Mark Y.; Drum, Chester L.
ABSTRACT: Introduction : Thymosin beta-4 (TB4) is an endogenous peptide with protective and regenerative effects in models of cellular and organ injury. TB4 is increasingly measured as a potential plasma or serum biomarker in human cardiovascular, liver, infectious, and autoimmune disease. Areas covered : The focus of this review is the quantification of TB4 in clinical cohort studies and whether reported TB4 concentrations differ with respect to method of sample preparation. We survey current literature for studies measuring TB4 in human serum or plasma and compare reported concentrations in healthy controls. Expert opinion : We find substantial intra- and inter- study variability in healthy controls, and a lack of protocol standardization. We further highlight three factors that may confound TB4 clinical measurements and should be considered in future study design: 1) residual platelets remaining in suspension after centrifugation, 2) TB4 release following ex vivo platelet activation, and 3) specificity of assays towards posttranslational modifications. Accordingly, we put forth our recommendations to minimize residual and activated platelets during sample collection, and to cross-validate TB4 measurements using both antibody-based and mass spectrometry-based methods.